The prevalence and correlates of childhood trauma in patients with early psychosis. (July 2015) - Duhig, Michael; Patterson, Sue; Connell, Melissa; Foley, Sharon; Capra, Carina; Dark, Frances; Gordon, Anne; Singh, Saveena; Hides, Leanne; McGrath, John J; Scott, James
Objective: To describe the prevalence and demographic, clinical and functional correlates of childhood trauma in patients attending early psychosis clinics. Method: Participants were recruited from outpatients attending four early psychosis services. Exposure to childhood trauma was assessed using the Childhood Trauma Questionnaire (CTQ). Psychopathology was measured using the Positive and Negative Syndrome Scale and the Depression, Anxiety and Stress Scale. Social and vocational functioning and substance use were also assessed. Results: Over three-quarters of the 100 patients reported exposure to any childhood trauma. Emotional, physical and sexual abuse were reported by 54%, 23% and 28% of patients, respectively, while 49% and 42% of patients reported emotional and physical neglect, respectively. Female participants were significantly more likely to be exposed to emotional and sexual abuse. Exposure to childhood trauma was correlated with positive psychotic symptoms and higher levels of depressive, anxiety and stress symptoms; however, it had no impact on social or vocational functioning or recent substance use. Conclusion: Exposure to childhood trauma was common in patients with early psychosis, and associated with increased symptomatology. Existing recommendations that standard clinical assessment of patients with early psychosis should include inquiry into exposure to childhood trauma are supported.